Ethylene Enhances Seed Germination and Seedling Growth Under Salinity by Reducing Oxidative Stress and Promoting Chlorophyll Content via ETR2 Pathway - Wang, Yue; Diao, Pengfei; Kong, Lingqi; Yu, Ruonan; Zhang, Man; Zuo, Tiantian; Fan, Yanyan; Niu, Yiding; Yan, Fang; Wuriyanghan, Hada (Frontiers in Plant Science, 2020)
Alfalfa (Medicago sativa L.) is an important forage, and salinity is a major stress factor on its yield. In this study, we show that osmotic stress retards alfalfa seedling growth, while ionic/oxidative stress reduces its seed germination. Ethylene treatment can recover the germination rate of alfalfa seeds under salt stress, while ethylene inhibitor silver thiosulfate exacerbates salt effects. ETH reduces the accumulation of MDA and H2O2 and increases POD activity. ETH and ACC improve the salt tolerance of alfalfa by increasing proline content under salt stress. In contrast, STS inhibits alfalfa seed germination by reducing POD activity. NaCl treatment reduces chlorophyll content in alfalfa leaves, while ETH and ACC can increase the chlorophyll content and promote seedling growth. ETH promotes the growth of alfalfa in saline condition by reducing the expression of MsACO and MsERF8 genes, while increases its germination rate by upregulating MsERF11 gene. Silencing of MsETR2, a putative ethylene receptor gene in alfalfa, abolishes ethylene triggered tolerance to salt stress. In summary, we show that ethylene improves salt tolerance in alfalfa via MsETR2 dependent manner, and we also analyze the regulatory mechanism of ethylene during germination of alfalfa seeds under salt stress.